Caracterización de allullas enriquecidas con harina de amaranto (amaranthus caudatus) y lactosuero. - Cachaguay Ruiz, Odalis Najeli (2023)
The projects aim to evaluate the effect of adding amaranth flour and whey on the physical, chemical, sensory, and nutritional properties of allullas. For this, different treatments were prepared from the mentioned products, based on the formulation of a traditional allulla. The experimental design of two factors A x B was used at random, for factor A the concentration levels of amaranth flour and wheat flour were used, while in factor B there is the liquid component water or whey. To determine the best treatment, humidity analysis was carried out according to the NTE INEN 3084 standard in the laboratories of the Technical University of Cotopaxi, likewise, a sensory analysis developed on 20 tasters in parameters like taste, smell, color, texture and acceptability, resulting in t2, contains 20g of amaranth flour, 80g of wheat flour and 35ml of whey. The nutritional and microbiological analyzes were carried out in the SETLAB laboratory of the city of Riobamba to compare a traditional allulla and the allulla t2 in which 7.78% protein was obtained in the control allulla while in the t2 8.04 % protein, 3.24% fat in the control allulla while in t2 3.19% fat, 1.08% ash in the control allulla while in t2 1.83% ash, 98, 92% organic matter in the control allulla while in t2 98.17% organic matter, 41.38% nitrogen-free extract in the control allulla while in t2 40.830% nitrogen-free extract. The microbiological tests of the control allulla and allulla t2 were the same results, yielding as a result, Escherichia coli UFC/g< 10 and Salmonella CFU/g in Absence, shows that the control allulla and allulla t2 are suitable for human consumption because it does not have harmful microorganisms that affect health, and likewise the nutritional analysis shows that allulla t2 it is more nutritious than the control allulla.